Economic Hardship Among Elderly And Its Consequences Toward Cognitive Status. - J., Masud; T. A., Hamid (Archives of Business Research, 2017)
Objectives: The purpose of this study is to identify factors contributing to economic hardship and its consequences toward cognitive status among elderly in Malaysia. Design: the study is a cross-sectional study through personal interview. Setting: Data for this study were obtained from the project ‘Identifying Psychosocial Risks and Quantifying the Economic Costs of Age-Related Cognitive Decline among Older Malaysians’, funded by Malaysia Government through long term grant scheme (LRGS) in 2015. Participants: A total of 2321 elderly from Perak, Johor, Kelantan and Selangor state were involved in the study. Measurement: Economic hardship scale and Mini-Mental State Examination (MMSE) were used in this analysis. Logistic regression was conducted to identify factors that contribute toward economic hardship of elderly and a Chi-square analysis was used to examine the association between economic hardship and cognitive status. Results: Logistic regression revealed that four predictors significantly contributed toward explaining the likelihood of experiencing economic hardship. The factors were ethnicity, education level, sources of income and household poverty status. Malay, elderly with no formal schooling, those with no earned income and living in a poor household (household income less than RM930), were more likely to experience economic hardship than their counterpart. The chi-square analysis revealed that higher proportion of those experienced economic hardship were reported having cognitive impairments (severe, moderate and mild). Conclusion: The study provides new insight into the impact of economic hardship on cognitive status of older persons particularly in developing countries such as Malaysia.